2021
DOI: 10.3390/pathogens10081028
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of a Rhesus Macaque Model for Scrub Typhus Transmission: Pilot Study to Evaluate the Minimal Orientia tsutsugamushi Transmission Time by Leptotrombidium chiangraiensis Chiggers

Abstract: Recently, an intradermal inoculation of the rhesus macaque model of scrub typhus has been characterized at our institution. The current project was to establish a rhesus macaque model of scrub typhus using the naturally infected chigger challenge method that faithfully mimics the natural route of pathogen transmission to fully understand the host-pathogen-vector interactions influencing pathogen transmission. Unlike the needle-based inoculation route, Orientia tsutsugamushi-infected chiggers introduce both pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…G-CSF is a growth factor that stimulates the bone marrow to produce granulocytes, such as neutrophils and release them into the bloodstream [59]. Increased G-CSF levels in the blood have been reported in a rhesus macaque model of scrub typhus [60]. Our recent study revealed that virulent Karp infection can induce higher levels of G-CSF than the less virulent Gilliam infection [18], indicating that G-CSF might be related to the hyperinflammation and immunopathology.…”
Section: Plos Pathogensmentioning
confidence: 88%
“…G-CSF is a growth factor that stimulates the bone marrow to produce granulocytes, such as neutrophils and release them into the bloodstream [59]. Increased G-CSF levels in the blood have been reported in a rhesus macaque model of scrub typhus [60]. Our recent study revealed that virulent Karp infection can induce higher levels of G-CSF than the less virulent Gilliam infection [18], indicating that G-CSF might be related to the hyperinflammation and immunopathology.…”
Section: Plos Pathogensmentioning
confidence: 88%
“…G-CSF is a growth factor that stimulates the bone marrow to produce granulocytes, such as neutrophils and release them into the bloodstream[55]. Increased G-CSF levels in the blood have been reported in a rhesus macaque model of scrub typhus[56]. Our recent study revealed that virulent Karp infection can induce higher levels of G- CSF than the less virulent Gilliam infection[18], indicating that G-CSF might be related to the hyperinflammation and immunopathology.…”
Section: Discussionmentioning
confidence: 99%
“…Rhesus monkeys (Macaca mulatta) are the most common NHP used in biomedical research [4]. Recently, this NHP species has been used especially as a model for COVID-19 [5] and scrub typhus transmission studies [6].…”
Section: Introductionmentioning
confidence: 99%